The Market Hall, Johannesburg - Unknown (My University, 2011)
The Market Hall on the left, the Colonial Trust Building and the African City Property Trust Building in the Centre. Date Unkown.
Black and White photo.
Keywords: The Market Hall, Colonial Trust Building, African City Property Trust building, Johannesburg.